Cortisol promotes breast‐to‐brain metastasis through the blood‐cerebrospinal fluid barrier. Issue 4 (26th February 2021) - Herrera, Robert A.; Deshpande, Krutika; Martirosian, Vahan; Saatian, Behnaz; Julian, Alex; Eisenbarth, Rachel; Das, Diganta; Iyer, Mukund; Neman, Josh
Abstract: Background: Elevated basal cortisol levels are present in women with primary and metastatic breast cancer. Although cortisol's potential role in breast‐to‐brain metastasis has yet to be sufficiently studied, prior evidence indicates that it functions as a double‐edged sword—cortisol induces breast cancer metastasis in vivo, but strengthens the blood‐brain‐barrier (BBB) to protect the brain from microbes and peripheral immune cells. Aims: In this study, we provide a novel examination on whether cortisol's role in tumor invasiveness eclipses its supporting role in strengthening the CNS barriers. We expanded our study to include the blood‐cerebrospinal fluid barrier (BCSFB), an underexamined site of tumor entry. Methods and Results: Utilizing in vitro BBB and BCSFB models to measure barrier strength in the presence of hydrocortisone (HC). We established that lung tumor cells migrate through both CNS barriers equally while breast tumors cells preferentially migrate through the BCSFB. Furthermore, HC treatment increased breast‐to‐brain metastases (BBM) but not primary breast tumor migratory capacity. When examining the transmigration of breast cancer cells across the BCSFB, we demonstrate that HC induces increased traversal of BBM but not primary breast cancer. We provide evidence that HC increases tightness of the BCSFB akin to the BBB by upregulating claudin‐5, a tight junction protein formerly acknowledged as exclusive to the BBB. Conclusion: Our findings indicate, for the first time that increased cortisol levels facilitate breast‐to‐brain metastasis through the BCSFB—a vulnerable point of entry which has been typically overlooked in brain metastasis. Our study suggests cortisol plays a pro‐metastatic role in breast‐to‐brain metastasis and thus caution is needed when using glucocorticoids to treat breast cancer patients.